Optimalisasi Tata Kelola Badan Usaha Milik Desa 'Makmur' dalam Pengembangan Sektor Pariwisata Desa Jetak - Priambudi, Anung Satria; Prathama, Ananta (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This research aims to evaluate the governance of the village-owned enterprise (BUMDesa) "Makmur" in managing the tourism sector in Jetak Village. Effective BUMDesa governance requires various efforts to ensure good tourism management and provide solutions if problems arise. This research uses a qualitative method with a descriptive approach. The data collected came from primary and secondary sources, with data collection techniques through observation, interviews, and documentation. Based on Purnomo's theory, the analysis results show that the management of the tourism sector by BUMDesa "Makmur" still faces several obstacles, mainly because the BUMDesa governance indicators have not been fully implemented. Therefore, BUMDesa needs periodic assessments to optimize tourism management.